Vascular malformations in pediatric patients: 10-year experience of a vascular anomalies clinic - Sofía Valdés-Loperena; Adolfo E. Lizardo-Rodríguez; Carlos G. Hinojosa-Gutiérrez; Max A. Bernal-Moreno; Gerardo A. Montejo-Ruiz; Manuel Guerrero-Hernández; Jaime Shalkow-Klincovstein; Rodrigo Díaz-Machorro; Daniel Hernández-Arrazola; José M. Palacios-Acosta; Oscar Colín-Martínez; Gerardo Fernández-Sobrino; et al. (Permanyer, 2024)
Background: Vascular malformations (VaMs) are caused by errors in vascular morphogenesis. Diagnosis and treatment can be complex. Few specialized centers care for these patients, and limited literature exists regarding their characteristics and clinical course. The vascular anomalies clinic (VAC) at the Instituto Nacional de Pediatría (National Institute for Pediatrics) is a multidisciplinary team and has been a reference center for patients with VaMs since 2012. We sought to describe the characteristics of patients cared for at the VAC, types of VaMs, treatments used, and clinical course. Methods: This was a descriptive, observational, retrospective, and cross-sectional study conducted from 2012 to 2022. Results: We included 435 patients with VaMs; the median age of presentation was 1 month. The most frequent signs and symptoms were increased volume (97.2%), superficial color change (65.5%), and pain (43.3%). The most common VaMs were lymphatic (36.7%) and venolymphatic (18.3%). Sclerotherapy was the most frequent treatment (73.4%), followed by medical treatment with sirolimus (18.5%); response to both was excellent/good in > 85% of cases. Conclusion: In this retrospective study of children with VaMs, we found that low-flow malformations were the most common, and sclerotherapy and sirolimus were the most frequently used treatments. The therapeutic response was excellent/good in most cases.